Efficacy, Safety, and Quality of Treatment Satisfaction of Premixed Human and Analogue Insulin Regimens in a Large Cohort of Type 2 Diabetic Patients: PROGENS BENEFIT Observational Study - Katarzyna Nabrdalik; Hanna Kwiendacz; Tomasz Sawczyn; Andrzej Tomasik; Michał Kukla; Małgorzata Masierek; Janusz Gumprecht (International Journal of Endocrinology)
Diabetes is a lifelong course disease, so insulin treatment has to be effective and safe, and patients should be satisfied with it. We aimed to compare efficacy, safety, and quality of treatment satisfaction of human and premixed analogue insulin among 3264 patients (53.58% women) with type 2 diabetes mellitus (T2DM) in a real-life environment. 2493 patients (62.77%) had been assigned to group I where before the inclusion into the study the treatment regimen has been changed from analogue to human premixed insulin and 771 patients (37.23%) to group II where the treatment with insulin analogue remained unchanged. At the end of the study, there was a reduction of HbA1c observed in both of the groups; however, Δ HbA1c was significantly higher in group 1 (−0.599 versus −0.406; P<0.001 at visit 3 versus visit 1). The number of hypoglycemic episodes during the study observation was insignificantly reduced in both groups. Diabetes treatment satisfaction measured with DTSQ increased at the end of the study and was significantly better in group I compared to group II (P<0.001). This observational study proved that both human and premixed analogue insulin are effective and safe, and patients are satisfied with the treatment.